2012
DOI: 10.1136/bcr-2012-006629
|View full text |Cite
|
Sign up to set email alerts
|

Refractory calcinosis in a patient with dermatomyositis: response to intravenous immune globulin

Abstract: Dermatomyositis is an inflammatory myopathy and commonly presents with progressive, symmetric proximal muscle weakness and cutaneous findings. Calcinosis is a severe manifestation that can be debilitating. The cutaneous manifestations of dermatomyositis may also develop in the absence of detectable muscle disease, and can persist after the successful treatment of myositis. The author reports a 30-year-old woman with biopsy-proven dermatomyositis who had failed previous trials of azathioprine and methotrexate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…There is no specific treatment for the management of calcinosis cutis. Several case reports have highlighted the benefits of aluminium hydroxide, alendronate, intravenous immunoglobulin or electric shock wave lithotripsy . Teriparatide [rhPTH(1–34)], which is approved for the treatment of osteoporosis, is a recombinant form of PTH that stimulates osteoblast activity and inhibits osteoblast apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no specific treatment for the management of calcinosis cutis. Several case reports have highlighted the benefits of aluminium hydroxide, alendronate, intravenous immunoglobulin or electric shock wave lithotripsy . Teriparatide [rhPTH(1–34)], which is approved for the treatment of osteoporosis, is a recombinant form of PTH that stimulates osteoblast activity and inhibits osteoblast apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports have highlighted the benefits of aluminium hydroxide, alendronate, intravenous immunoglobulin or electric shock wave lithotripsy. [10][11][12][13][14] Teriparatide [rhPTH(1-34)], which is approved for the treatment of osteoporosis, is a recombinant form of PTH that stimulates osteoblast activity and inhibits osteoblast apoptosis. In the medical literature, only three cases of calciphylaxis in patients receiving treatment with teriparatide have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Shahani reports successfully treating a 30-year-old patient with DM with painful calcinosis who failed steroid, and several DMARDs and responded to 2 gm/kg/month-IVIg over two consecutive days [49]. A survey on pediatric rheumatologist suggested that just over 1/4th rheumatologists perform initial screening imaging for calcinosis in newly diagnosed IIM patients.…”
Section: Value Of Ivig In Myositis Calcinosis Cutis and Calcinosismentioning
confidence: 99%
“…The beneficial effect of IVIG in refractory, flared-up, rapidly progressive, or severe PM/DM has been documented in many open-label trials and reports (LOE2). [ 263 264 265 ]…”
Section: Intravenous Immunoglobulin (Ivig)mentioning
confidence: 99%